The MODULAR SPICE CONTAINER SYSTEM FOR ENHANCING COOKING EFFICIENCY: modular system, kitchen efficiency, cooking activity, ergonomic design, small kitchen - Hugo Daniswara; Mesah Nur Sejati (Penerbit Itenas, 2025)
The efficiency of spice storage remains a significant challenge, particularly for small kitchens in households and small businesses. This study aims to explore user experiences in implementing modular spice container systems, focusing on time efficiency, space organization, and ease of use. A qualitative approach was employed, including in-depth interviews, observations, and comprehensive literature reviews. The study involved 20 respondents from urban households and small business operators. Findings reveal that modular systems enhance storage efficiency by simplifying spice access, reducing kitchen clutter, and supporting more practical management. However, challenges such as container cleaning and size flexibility persist. This research recommends the development of more ergonomic and adaptive designs to meet users' daily needs effectively. Keywords: modular system, kitchen efficiency, cooking activity, ergonomic design, small kitchen